Insuring countries against natural disasters: Pool rules - Clarke, Daniel J.; Hill, Ruth Vargas (International Food Policy Research Institute, 2013)
In this brief, we summarize the key lessons that have emerged from a cost-benefit analysis of the African Risk Capacity (ARC) pool and discuss how these lessons can be more broadly applied to other cross-country pools.